ANALISIS PENGARUH VOTALITAS KAS, BESARAN AKRUAL, VOTALITAS PENJUALAN, LEVERAGE, SIKLUS OPERASI, UKURAN PERUSAHAAN, UMUR PERUSAHAAN, DAN LIKUIDITAS TERHADAP KUALITAS LABA - Purwanti, Titik (Kiat Bisnis, 2012)
AbstractThis research aims to test empirically The Effect of Cash Volatility, Accrual Magnitude, Sale Volatility, Leverage, Operation Cycle, Firm Size, Firm maturity, and Liquidity with Earning Quality. The conclution of this research are: Cash Volatility decisions positively affects the Earning Quality value regression coefficient is 0,79 and level significance is of 0,562, Accrual Magnitude decisions positively affects the Earning Quality value regression coefficient is 0,000 and level significance is of 0,919, Sale Volatility decisions positively affects the Earning Quality value regression coefficient is 0,121 and level significance is of 0,001, Leverage decisions negatively affects the Earning Quality value regression coefficient is -0,036 and level significance is of 0,033, Operation Cycle decisions positively affects the Earning Quality value regression coefficient is 0,000 and level significance is of 0,050, Firm Size decisions negatively affects the Earning Quality value regression coefficient is -0,004 and level significance is of 0,713, Firm Maturity decisions positively affects the Earning Quality value regression coefficient is 0,000 and level significance is of 0,460, Liquidity decisions negatively affects the Earning Quality value regression coefficient is -0,000 and level significance is of 0,003 Keywords:       Effect of Cash Volatility, Accrual Magnitude, Sale Volatility, Leverage, Operation Cycle, Firm Size, Firm Maturity, and Liquidity, Earning Quality